PEMURNIAN MINYAK GORENG BEKAS MENGGUNAKAN ADSORBEN BIJI ALPUKAT TERAKTIVASI - Fitriani, Fitriani (Jurnal Pendidikan Matematika dan IPA, 2018)
Abstract This research had been conducted in the use of avocado seed powder (Persea americana Mill) as an adsorbent to reduce peroxide and free fatty acids of the used cooking oil. The aim of  this research was to determine the best activator of avocado seed powder as an adsorbent to reduce peroxide and free fatty acids of the used cooking oil. This research used the variation of activators, consist of  hydrochloric acid (HCl), citric acid (C6H8O7), sodium chloride (NaCl) and sodium hydrogen phosphate (Na2HPO4) solutions. The result showed that the best activator of avocado seed powder by HCl which gave the highest free fatty acid reduction was 0,26%. Meanwhile, the best activator of avocado seed powder by C6H8O7 which gave the highest peroxide value reduction was 1,8 Meq/Kg . These results had qualified as the maximum limits of SNI cooking oil were 0.3% for the concentration of free fatty acids and 2 Meg/kg for the peroxide value of cooking oil. Keywords: adsorbent, avocado seed powder, used cooking oil